The role of educational neglect in modifying the behavior of middle school students from the point of view of teachers - Dr. Arkan Muhammad Ali (Journal of College of Education, 2023)
The study aimed to identify the concept of educational neglect, its types, and the role of educational neglect in modifying the behavior of middle school students from the point of view of teachers. The study adopted the descriptive approach, and the size of the research sample was (80) male and female teachers distributed among four schools. The researcher prepared a questionnaire consisting of: (23) in its initial form and after final amendments by experts, and the number of paragraphs became (15) in its final form.One of the most important results is identifying the prophetic methods in dealing with students, directing educators in the actual application of these prophetic methods in modifying behavior, explaining the truth about negligence, its role, importance and status, and explaining the effects of its application on the individual and society. The prophets, peace be upon them, applied the character of negligence in several situations and it had Great fruits. Also, one of the results of the research was that the Holy Qur’an called for ignoring the meaning, reference, and allusion, and it was not mentioned explicitly in the verses of the Holy Book of God. Among the most important recommendations was the interest in learning about the concept of educational neglect, and its application in the field of education, whether at home or in school, and the necessity of developing educational programs for parents and educators so that they are special curricula that contain studies that clarify the effect of educational neglect on modifying the behavior of middle school students
Keywords: educational neglect, behavior modification , Middle school, teachers